Impact of municipal solid waste amendments on molybdenum bioaccumulation in soil and vegetables: Health risk and bioavailability assessment - Asma Ashfaq; Zafar Iqbal Khan; Kafeel Ahmad; Ijaz Rasool Noorka; Hafsa Memona; Umbreen Bibi; Farzana Siddique; Hafiza Memona Nazir; Muhammad Kamran (International Journal of Applied and Experimental Biology)
This study examines the effects of municipal solid waste (MSW) amendments on molybdenum (Mo) concentrations in both soil and vegetables in two growing years. Three MSW treatments were tested, i.e., 25% MSW + 75% garden soil (T1), 50% MSW + 50% garden soil (T2), and 75% MSW + 25% garden soil (T3), with a control treatment of 100% garden soil (T0). Fifteen vegetable species were cultivated to evaluate Mo uptake and bioaccumulation. The Pollution Load Index (PLI) and Bioaccumulation Factor (BCF) values confirmed the impact of MSW on Mo accumulation in both soil and vegetables, with Allium cepa and Mentha arvensis showing greater sensitivity to Mo contamination. Health risk assessments revealed that vegetables grown in MSW-amended soils, especially Allium cepa at T3 Year-1, had higher Daily Intake of Metal (DIM) and Health Risk Index (HRI) values compared to those grown in the control soil. The analysis of molybdenum concentrations in blood samples taken from people of various localities added a human health aspect to the study. This study highlights the potential of MSW compost in increasing Mo bioavailability and the implications for human health through vegetable consumption, emphasizing the need to carefully monitor Mo levels in MSW-amended soils.